2019
DOI: 10.3390/medicina55080430
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension is the Prominent Risk Factor in Cataract Patients

Abstract: Background and objectives: The purpose of this study is to determine the impact of the most prominent cardiovascular and metabolic risk factors in patients undergoing cataract surgery. Materials and Methods: The study included 812 consecutive patients undergoing unilateral, uneventful cataract surgery by means of phacoemulsification, at the 2nd Department of Ophthalmology, Medical School, Aristotle University of Thessaloniki, Greece, during a calendar year. Patients were assessed for the type of cataract and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 17 publications
1
12
0
1
Order By: Relevance
“…[7] According to a study that included 812 consecutive patients undergoing unilateral, uneventful cataract surgery in Greece from 2018 to 2019, hypertension is the prominent risk factor in cataract patients. [8] Several studies have indicated that cataract formation occurs at an earlier age and more often in diabetic patients than in nondiabetic patients. For example, some studies have demonstrated that cataracts are three to four times more prevalent in patients with diabetes under the age of 65 [9][10][11][12].…”
Section: Comorbiditiesmentioning
confidence: 99%
“…[7] According to a study that included 812 consecutive patients undergoing unilateral, uneventful cataract surgery in Greece from 2018 to 2019, hypertension is the prominent risk factor in cataract patients. [8] Several studies have indicated that cataract formation occurs at an earlier age and more often in diabetic patients than in nondiabetic patients. For example, some studies have demonstrated that cataracts are three to four times more prevalent in patients with diabetes under the age of 65 [9][10][11][12].…”
Section: Comorbiditiesmentioning
confidence: 99%
“…This finding, however, requires more evidence and the enrollment of smoking patients in the study. Arterial hypertension is one of the other possible contributors to the etiopathology of cataracts, especially the posterior subcapsular subtype [50,51]. In the present study, we Arterial hypertension is one of the other possible contributors to the etiopathology of cataracts, especially the posterior subcapsular subtype [50,51].…”
Section: The Statistically Significant Inter-correlationsmentioning
confidence: 59%
“…Arterial hypertension is one of the other possible contributors to the etiopathology of cataracts, especially the posterior subcapsular subtype [50,51]. In the present study, we Arterial hypertension is one of the other possible contributors to the etiopathology of cataracts, especially the posterior subcapsular subtype [50,51]. In the present study, we observed significantly higher levels of tin (Sn) and ruthen (Ru), while titanium (Ti) levels (mean: 0.096 ppm, vs. 0.152 ppm for studied and control group, respectively, p = 0.045) were reduced in the AH of patients diagnosed with hypertension when compared with patients without this disorder (Figure 6).…”
Section: The Statistically Significant Inter-correlationsmentioning
confidence: 99%
“… 35 , 37 , 38 The finding that diabetes mellitus is associated with an increase in lens thickness is also consistent to reports of diabetes mellitus being associated with higher rates of cataract. 39 In addition to diabetes mellitus, hypertension is not only an important risk factor for cataract formation, 40 , 41 but also may even aggravate the negative impact of diabetes mellitus on cataract progression. 42 A study by Lee et al 43 reported that hypertension exacerbate cataract formation by modifying protein secondary structures in the lens capsule, thereby causing alteration of membrane transport and permeability for ions.…”
Section: Discussionmentioning
confidence: 99%